The Effects of In Ovo Injection of Synbiotics on the Early Growth Performance and Intestinal Health of Chicks - Duan, Ao-yi; Ju, An-qi; Zhang, Ying-nan; Qin, Yan-jun; Xue, Li-gang; Ma, Xin; Luan, Wei-min; Yang, Shu-bao (Frontiers in Veterinary Science, 2021)
This study evaluated the effect of synbiotics inclusion at the intra-amniotic stage in the layer chicks on different parameters such as performance, immunological function, intestinal development, and cecal microflora. 1200 eggs with fertile embryos were divided into four treatment groups. For every treatment, five replicates were used while 60 eggs were used per replicate. The four treatment groups were as follows: Non-injected group, 0.9% physiological saline injection (saline) group, 1×106 cfu/egg Lactobacillus plantarum injection (probiotic) group, and 1×106 cfu/egg L.plantarum+2 mg/egg Astragalus polysaccharide (synbiotic) group. In ovo injection was carried out on 18.5 day of embryonic age. The results showed that in ovo injection of probiotic or synbiotics did not affect the hatching and growth performance of the chicks but significantly increased the feed intake (FI) and body weights (BW), and promoted the feed conversion ratio (FCR). Also, in ovo injection of synbiotics could enhance the concentrations of serum interleukin-2 (IL-2), interferon-γ (IFN-γ), intestinal lavage fluid secretory immunoglobulin A (SIgA) along with histomorphological development of the small intestine. Our results also indicated that intra-amniotic synbiotics injection significantly increased the Lactobacillus and Bifidobacterium colonization while decreasing the relative abundance of Escherichia coli (E. coli) in the chicken cecum (P < 0.05). In summary, in ovo injection of synbiotics had positive impacts on the performance, immunological function, gut development, and microbiota of growing chicks.